Iwokrama business plan 2006-2010 ([The Centre] [Georgetown]GY, 2006)
Presents Iwokrama's new plan for greater partnership with the institutions and investors which are committed to playing their own part in reponding to climate change.
Keywords: TROPICAL FORESTS